The Knowledge Base of the National Rare Ancient Book Directory (2023)
The Knowledge Base of the National Rare Ancient Book Directory (La base de connaissances du catalogue national des livres anciens rares) : le Catalogue national des ouvrages anciens rares (Guójiā Zhēnguì Gǔjí Mínglù 國家珍貴古籍名錄 en chinois), incluant six listes bibliographiques approuvées par le Conseil des affaires de l’État de la République populaire de...
Keywords: _open access